PENERAPAN METODE KOOPERATIF TIPE NHT (Numbered Heads Together) DALAM MENANGGAPI CERITA PERISTIWA DI KELAS V SDN SUKAJADI II KECAMATAN LEMAHSUGIH KABUPATEN MAJAENGKA - Wirawati, Vina Silviana; Iswara, Prana Dwija; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2017)
Based on the observations on the students of grade V of SDN Sukajadi II about listening to respond to stories about the events of students are still experiencing difficulties. With this problem, classroom action research (PTK) is done by using Kemmis and Taggart research by applying NHT method with audio media. In the study there are several assessment instruments, planning and implementation of teacher performance, student activities and student learning outcomes. Planning is structured according to the problems found in the previous data. Implementation of learning is made with three stages of the initial activity, the core and the end of the kingdom. Student learning outcomes have not reached the specified target, but in each cycle has increased. In the first cycle only 60% of the students completed, the third cycle increased more to 75% and the third cycle has increased to 100%.